HUBUNGAN KEPRIBADIAN INTROVER DENGAN KECEMASAN SOSIAL PADA MAHASISWA IAIN PALANGKA RAYA - Fiana Mahmudah; Desi Erawati; Ihsan Mz (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2021)
Social anxiety is a condition which can result guilty feeling, afraid of making mistakes, low self-confidence, and avoiding negative views of others. Introvert students are often thought as a closed personality in social interaction. This study aims to identify the relationship between introvert personality and social anxiety in Islamic State Institute of Palangka Raya (IAIN) students. This type of research is corelational quantitative. Respondents involved in this study were 195 people. The 2017 generation of IAIN Palangka Raya students was considered homogeneous, thus using simple random sampling technique. The questionnaire used is an EPI scale and the SAS-A scale. The results showed that 99 students from four faculties have introvert personality consisting of 21 male and 78 female students. Students with introvert personality experienced social anxiety in the lower category consisted of 6 respondents (6.1%), the medium category 60 (60,6%) and the high category 33 (33.3%). The relationship between introvert personality and social anxiety obtained a correlation coefficient of -0.293 which in the low category. The value of rcount is higher than rtable (-0.293>-0.198). The significance value of 0.003 is smaller than 0.05 (0.003 <0.05). The (-) sign before the correlation number indicates non-directional correlation. Thus there is a significant negative correlation between introvert personality and social anxiety in IAIN Palangka Raya students.